Joseph Butler's moral and religious thought : tercentenary essays - Cunliffe, Christopher (Oxford [England] : Clarendon Press ; Oxford ; New York : Oxford University Press, 1992)
The essays in this book mark the tercentenary of the birth of Bishop Joseph Butler, the leading theologian of the Church of England in the 18th century and also an important moral philosopher. Thirteen distinguished contributors cover the full range of Butler's theological and philosophical writings--from his Christian apologetic against the deists to his discussion of the role of conscience in the moral agent--as well as setting them in their historical context and suggesting their relevance to contemporary religious and philosophical issues. At a time when there is a renewed interest in Butler's thought as well as in the theological positions he was opposing, it is both timely and appropriate that these detailed studies should not be made available. The Bishop of Durham has written a Foreword introducing the volume.
Butler on benevolence / David McNaughton -- Butler on God and human nature / Alan Millar.
Includes bibliographical references and index.
Keywords: Butler, Joseph, -- 1692-1752.